What is the effect of oral vinegar ingestion on postprandial glucose levels?. Issue 2 (February 2015) - Bradley, Juliet; Rodriguez, Vimarie; Gollapudi, Kranti
Abstract : Evidence‐Based Answer : The evidence is mixed. Preprandial oral ingestion of vinegar may reduce postprandial glucose levels by anywhere from 19% to 25%. Any such effect may be greater in combination with high‐glycemic index meals (SOR: C, RCTs with limited‐quality disease‐oriented evidence).